Electrically tunable mode-locked fiber laser using laser induced graphene assisted long-period fiber grating. (1st March 2023) - Zhu, Yuehong; Zhang, Hong; Wu, Zhujing; Shen, Li; Wang, Shutong; Deng, Guoliang; Zhou, Shouhuan
Abstract: We demonstrate an electrically tunable all-fiber mode-locked erbium-doped fiber laser using a long-period fiber grating (LPFG) assisted by laser induced graphene heaters (LIG-H). Wavelength tunability is achieved by the temperature-dependent transmission spectrum of the LPFG. The central wavelength can be continuously tuned from 1549.00 nm to 1563.63 nm with a spectral tuning range of 14.63 nm. The graphene on polyimide (PI) paper is fabricated using a 10.6 μ m CO2 laser, which has a maximum operating temperature of around 500 °C. The proposed LPFG-based electrical tunability of mode-locked fiber laser provides a novel, repeatable, simple, and cost-effective laser tuning technique.